THU0368 IL-22 Impact on Human Bone Marrow Mesenchymal Stem Cells Functions; A Novel Pathway That May Contribute To Aberrant New Bone Formation in Human SPA. (15th July 2016) - El-Sherbiny, Y.; El-Zayadi, A.; Churchman, S.; Baboolal, T.; Cuthbert, R.; El-Jawhari, J.; Alase, A.; Badawy, A.; Jones, E.; McGonagle, D.
Abstract : Background: The spondyloarthropathies (SpAs) including ankylosing spondylitis (AS) show a propensity for florid new bone formation following bouts of inflammation. However, in other skeletal diseases such as rheumatoid arthritis, inflammation predictably leads to diffuse bone loss and periarticular erosion. 1 Anti-TNF therapies effectively alleviate spinal inflammation in SpA but fail to arrest the new bone formation. SpAs are genetically and therapeutically linked to IL-23, which in turn regulates IL-22. it is a master regulator of stem cell niches in the intestine, liver, endometrium and skin 2 but to the best of our knowledge, no data on its influence upon human osteoprogenitors or MSCs has been described. Objectives: We hypothesized that IL-22, a master regulator of stem cells in other niches, might also regulate mesenchymal stem cell (MSC) osteogenesis in an inflammation-dependent context. Methods: Bone marrow samples were obtained after informed consent (n=10), and MSCs isolated and culture expanded for 2–4 passages. Cells were analysed using flowcytometry for ISCT criteria and expression IL-22R ±IFNG and TNFa stimulation. IL-22 effects were tested with and without inflammatory cytokines (IFNG and TNFa) on: MSC proliferation using colorimetric XTT assay, MSC migration using transwell migration assays, the expression of trascriptional factors of MSC adipo-, osteo- or chondro-genic potential using qRT-PCR, and on osteogenic differentiation assay evaluated by colorimetric calcium assay. Results: Interestingly, IL-22R expression was detected in MSCs intracellularly and showed a mean 1.8±0.12 fold increase post IFNG and TNFa stimulation. MSC stimulation with combined IL-22, IFNG and TNFa but not single cytokines increased MSC proliferation (p=0.008) and migration (p=0.037) compared to unstimulated MSCs. Osteogenic, adipogenic but not chondrogenic transcription factors were upregulated by IL-22 (p<0.05). Moreover, Inflammatory stimuli (IFNG+TNFa±IL-22) did not affect the chondro- and adipogenic transcription factors but did temper the increase of pro-osteogenic RUNX2 . Mature bone markers, particularly BGLAP /osteocalcin were rarely detectable in the presence of inflammation. The inflammatory milieu also downregulated all tested chondrogenic markers ACAN, COL2A1 and COL10A1 compared to unstimulated and IL-22 stimulated MSCs. Notably, MSC osteogenesis was enhanced following IL-22 exposure (p=0.031 for calcium production). The combination of IFNG and TNFa with or without IL-22 suppressed MSC osteogenesis (p=0.0313 for both). Conclusions: This is the first study to show that IL-22 is involved in MSC proliferation/migration in inflammatory environments with MSC osteogenesis occurring only in IFNG/TNFa absence. Given the genetic link with SpA, these physiological MSC bone responses need evaluation in pathological post-inflammation osteogenesis in human SpA. References: Hreggvidsdottir HS, Noordenbos T, Baeten DL. Inflammatory pathways in spondyloarthritis. Mol Immunol 2014;57(1):28–37. Feng D, Kong X, Weng H, et al. Interleukin-22 promotes proliferation of liver stem/progenitor cells in mice and patients with chronic hepatitis B virus infection. Gastroenterology 2012;143(1):188–98 e7. Disclosure of Interest: None declared